A Time for Hope? Pursuing a Vision of a Fair, Sustainable and Healthy World. Issue 2 (14th April 2018) - Friel, Sharon
Abstract: The confluence of social and health inequities and global environmental degradation shines a light on fundamental ruptures in society. A systems view of humanity reminds us that this status quo is not static, and that the shifting political and economic sands provide an important window of opportunity to collectively change the system towards the public good, such that communities are able to live with good health, dignity and in an environmentally sustainable way. To enable this, global policy, and in particular global health policy must break out of the policy silos and refocus in a systems way. If the system is to adapt, an ambitious vision for the system is needed that is different to the status quo. No one regulatory model that can improve complex societal problems, rather we must use a plurality of approaches. Reorienting the system to achieve positive outcomes depends on reimagining the purpose of structural regulatory powers, and the releasing the agency of networks of concerned actors. In a hyper‐connected world there are many partners to help create systems of hope. Abstract : It would be very easy to be overwhelmed with despair given the dreadful atrocities that plague the world. No country is immune from these concerns but such life and death experiences are not distributed evenly between or within nations